LIGHTWEIGHT PLUGGING FLUIDS TO IMPROVE THE QUALITY OF WELL CEMENTING IN THE CONDITIONS OF THE VERKHNYOMASLOVETSKE FIELD OF PJSC “UKRNAFTA” - Stavychnyi Ye. М.; Femiak, Ya. M.; Vytiaz, O. Yu.; Tershak, B. A.; Ignatov, A. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Analyzing the literature and professional publications, it was found that a significant number of oil and gas fields in Ukraine are classified as hard-to-recover deposits. However, such fields provide a significant amount of production and are a reserve for increasing the production potential. The article provides a brief overview of mining and geological conditions and describes the peculiarities of well construction at the Verkhnyomaslovetske field of PJSC “Ukrnafta”, which belongs to the category of fields with hard-to-recover hydrocarbon reserves. The basic technological solutions were used for cementing production strings are analyzed. Based on the carried researches of typical lightweight plugging muds, the article reveals that these materials do not meet the conditions of high-quality casing and cementing, which is caused by violation of the technological parameters of the plugging mud and low strength characteristics of cement stone. Risks are characterized and disruptions of the technological process during cementing of production casings are identified. A new type of lightweight plugging material with a cement batter density of 1.25 g/cm3 was developed and the main technological parameters of the cement slurry and physical and mechanical properties of cement stone were researched. The designed plugging system was tested in accordance with the technological and thermobaric conditions of wells cementing in the Verkhnyomaslovetske field. The structure-forming features of the developed material were researched. The results of the researches indicate the stability of the plugging system and high strength characteristics of the lightweight plugging material. The X-ray fluorescence spectroscopy and X-ray structural analysis confirmed the forming of the main crystallizing phases of cement stone, which confirms the rapid kinetics of structure-forming of the designed plugging system. Carried complex researches and the obtained results indicate the advantages of the developed plugging material in terms of both technological and operational properties over the base materials.